Ultrasonic-assisted extraction as a green route for hydrolysis of bound phenolics in selected wild fruits: Detection and systematic characterization using GC–MS–TIC method. (December 2021) - Ahmad, Naveed; Zuo, Yuegang; Anwar, Farooq; Abbas, Ali; Shahid, Muhammad; Hassan, Adeel Ahmad; Bilal, Muhammad; Rasheed, Tahir
Graphical abstract: Highlights: Ultrasonic-assisted extraction as a green route for hydrolysis of bound phenolics. Separation and characterization of 21 phenolic compounds by GC–MS–TIC. Identification and quantification of twelve natural phenolic antioxidants in fruits of Olive and Jujube. Selected wild plants fruits contain natural phenolic compounds in free and bound forms. Effective technique for the recovery of conjugated phenolic compounds. Abstract: This research work reports ultrasonic-assisted hydrolysis and characterization of free and bound phenolics in fruits of two wild medicinal plants such as olive and jujube by using Gas Chromatography-Mass Spectrometry-Total Ion Current technique. The results of present study revealed the presence of seven to eleven phenolic compounds (free and bound form) in tested wild fruits. Among other phenolic acids detected, 2, 4-dihydroxybenzoic acid (62.19 mg/kg dry weight) and trans -cinnamic acid (31.41 mg/kg dry weight) were dominant in olive fruit, and in case of jujube fruit, 2, 3-dihydroxybenzoic acid and trans -cinnamic were detected to be the major phenolic acids at the levels of 10.00 and 7.71 mg/kg dry weight, respectively. In present research work, the ultrasonic-assisted hydrolysis represented an effective green process for release of bound phenolics from selected wild fruits. These results also advocate potential uses of tested wild fruits as promising source of valuable phenolic ingredients to be used for developing nutraceutical and functional food.